Employee Performance: Leadership Styles, Discipline and Motivation - Agnes Marisca Dian Sari (Dinasti International Journal of Management Science, 2023)
Leadership style is a factor that determines the development of an organization . Work discipline and motivation are determining factors of the employee’s performance. This study aims to describe and examine the influence of leadership style, discipline, and motivation variables on employee performance. The research object consists of the Online Library which are Google Scholar and some online media. The research method used library research from e-book and open access e-journal. The results in this study are Leadership Style, Discipline, and Motivation have a positive effect on employee performance.